Shifting paradigms in the treatment of chronic lymphocytic leukemia. (February 2015) - Thompson, Philip A; Shpall, Elizabeth J; Keating, Michael J
ABSTRACT : The treatment of chronic lymphocytic leukemia (CLL) is evolving rapidly. Insight into the genetics and biology of the disease, including the importance of intracellular signaling pathways and interactions with the microenvironment has led to the development of rational targeted therapies which are having a major impact on the survival of patients with relapsed and high-risk disease. In addition, an exciting array of cellular therapies and immunotherapy options are in various stages of development. We review the current understanding of CLL genetics and biology, current treatment strategies in specific patient groups and opportunities for future treatment combinations which will bring the goal of cure or long-term disease control with minimal toxicity within reach for the majority of patients.